The perception and knowledge about episiotomy: A cross-sectional survey involving healthcare workers in a low- and middle-income country - Cyprian M. Maphanga; Thinagrin D. Naidoo (AOSIS, 2021)
Background: Episiotomy was introduced into clinical practice without clear evidence of its benefits.The knowledge and understanding of episiotomy guidelines and practice by healthcare workers is substandard in our setting; hence, the injudicious use of this procedure have led to high rates. Aim: To assess the knowledge, perception and practice of episiotomy by healthcare workers. Setting: Research was conducted in a Pietermaritzburg complex, South Africa Methods: A questionnaire-based survey was conducted amongst healthcare workers regarding episiotomy practice. In addition to providing demographic data, the participants were requested to respond to 35 proposed statements regarding episiotomy practice. Data were analysed using SPSS (Statistical Package for the Social Sciences) software. Results: One hundred and forty-two midwives and 66 medical practitioners completed the questionnaires. There were variations in responses to several statements on episiotomy practice by medical practitioners and nurses based on their level of experience. This study found that the majority of HCWs did not have access to a protocol or policy on episiotomy practice in their units; furthermore, nor knowledge of the South African guidelines for maternity care on episiotomy practice. Significantly, more medical practitioners felt a need for more in-service training and an increase in the number of episiotomies performed under supervision. The commonly reported reason for performing an episiotomy by both medical practitioners and midwives was to reduce 3rd - 4th degree perineal tears. Conclusion: Healthcare workers in our setting displayed poor knowledge about the practice of episiotomy and were not aware of existing national guidelines on episiotomy practice.